THE USE OF DIGITAL LEARNING MEDIA BASED ON THE SEESAW WEBSITE IN ASSESSING HISTORY LEARNING SKILLS AT SMA N 9 SIJUNJUNG: PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL BERBASIS WEBSITE SEESAW DALAM PENILAIAN KETERAMPILAN BELAJAR SEJARAH DI SMA N 9 SIJUNJUNG - Riska Novrianti Riska; Zulfa; Kaksim (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to analyze the effectiveness of the Seesaw website-based digital learning media in assessing history learning skills at SMA N 9 Sijunjung. The method used was a qualitative research with a case study approach, involving 11th-grade students and history teachers as research subjects. Data were collected through questionnaires distributed to students and in-depth interviews with teachers. The results showed that the use of Seesaw increased student engagement in the learning process, with an average percentage of learning activities reaching 90.19%. Students reported that the platform made it easier for them to access materials, collaborate in group discussions, and complete assignments more smoothly. Furthermore, teachers also found it easy to provide real-time feedback, which contributed to improving the quality of learning